Math

posted by .

prove:(cscx-cotx)^4 x (cscx+cotx)^4 = 1

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. calculus

    express in sinx 1 1 ---------- + -------- cscx + cotx cscx - cotx and express in cosx 1 + cot x ------- - sin^2x cscx = 1/sinx so what do i do w. that extra one on the top!?
  2. trig

    express this in sinx (1/ cscx + cotx )+ (1/cscx- cotx) i got 2sinx is that right?
  3. drwls

    My previous question: Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (secx/sinx)*(cotx/cscx) = (secx/cscx)(cotx/sinx) = (sinx/cosx)*cotx*(1/sinx) "The last steps should be obvious" Not to me. I can convert (sinx/cosx) to …
  4. Pre-Calculus

    Find a numerical value of one trigonometric function of x if tanx/cotx - secx/cosx = 2/cscx a) cscx=1 b) sinx=-1/2 c)cscx=-1 d)sinx=1/2
  5. Precalculus

    Simplify:[(cscx-cotx)(cscx+cotx)]/cscx
  6. Trigonometry

    prove:(cscx-cotx)^4 x (cscx+cotx)^4 = 1
  7. ap calc bc

    hi! ok, i know that deriv(cscx) = -cscxcotx and that deriv(cos) = -sinx deriv(cotx) = -((cscx)^2) my question is: is this (statements below) correct?
  8. Trig

    prove (cscx-secx/cscx+secx)=(cotx-1/cotx+1)
  9. trig

    Prove (cscx+cotx)(cscx-cotx)=1
  10. Math

    Im really struggling with these proving identities problems can somebody please show me how to do these?

More Similar Questions